2016
DOI: 10.1186/s13075-016-1133-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening for peptides targeted to IL-7Rα for molecular imaging of rheumatoid arthritis synovium

Abstract: BackgroundInterleukin-7 receptor alpha (IL-7Rα) represents a biomarker with potential applications in rheumatoid arthritis (RA) diagnosis and therapy. We have therefore searched by phage display potential IL-7Rα specific peptides with the primary goal being to develop in vivo molecular imaging tools.MethodsIL-7Rα-targeted peptides were searched within a disulfide-constrained combinatorial phage displayed library of random linear heptapeptides. The apparent dissociation constant (Kd) and half maximal inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…In addition, the circulating concentration of gal-1-targeted USPIO is too low due to the liver and spleen capture ( Figure 5). Indeed, our previous research on nanoparticles has shown a plasma concentration greater than 1000 µmol Fe/L at 90-120 min post-injection [54][55][56], whereas during this work, values ranging from about 400 µmol Fe/L (for USPIO-P1) to 700 µmol Fe/L (for USPIO-P7) were found.…”
Section: Detection Of Uspio Derivatives In Tumors Developed In Athymicontrasting
confidence: 55%
“…In addition, the circulating concentration of gal-1-targeted USPIO is too low due to the liver and spleen capture ( Figure 5). Indeed, our previous research on nanoparticles has shown a plasma concentration greater than 1000 µmol Fe/L at 90-120 min post-injection [54][55][56], whereas during this work, values ranging from about 400 µmol Fe/L (for USPIO-P1) to 700 µmol Fe/L (for USPIO-P7) were found.…”
Section: Detection Of Uspio Derivatives In Tumors Developed In Athymicontrasting
confidence: 55%
“…As shown by MRI and biodistribution data, the pattern of renal clearance of both Gd-DOTA-P88 and Gd-DOTA-Scramble is not significantly different, which suggests that xenograft enhancement by the specific compound is not a consequence of its delayed blood clearance. On the other hand, Gd-DOTA-P88 is less efficient in terms of NMR efficacy (i.e., relaxivity: r 1 of 4.57 s −1 mM −1 at 300 MHz and 37 °C for Gd-DOTA-P88) than superparamagnetic agents (i.e., r 2 of 92.93 s −1 mM −1 at 300 MHz and 37 °C for USPIO-P88 [ 14 , 15 ]), but the binding of functionalized paramagnetic compounds to their targeted biomarkers contributes to a substantial enhancement of their relaxivity due to the increase in the rotational correlation time [ 21 , 22 ]. Finally, the binding specificity of P88 was evaluated by using an in vitro competitive assay.…”
Section: Discussionmentioning
confidence: 99%
“…This initial study, however, was (1) restricted to a non-physiological cell model, unrelated to beta cells [ 13 ], and (2) P88 was conjugated to a contrast agent (CA) that produces a negative contrast on MRI. This CA is partially excreted via the reticuloendothelial system (RES) despite a poly (ethylene glycol) (PEG) coating [ 14 , 15 ]. This RES uptake, in combination with the well-known macrophage infiltration of pancreatic islets, may cause an inaccurate BCM reading [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have verified that specific peptide can be linked with USPIO for molecular MR imaging and the peptide properties and functionality as well as the relaxation abilities of USPIO nanoparticles can also be remained [ 28 ]. Our research also demonstrated that the targeted peptide (CKGGRAKDC-NH2) conjugated with USPIO can also retain its affinity for BAT.…”
Section: Discussionmentioning
confidence: 99%